Usulan penerapan Industri 4.0 untuk rantai pasok dan logistik cerdas di perusahaan injection moulding - Hendri Hendri; Sally Cahyati (Universitas Mercu Buana, 2021)
Currently, the industrial era 4.0 coincides with the covid 19 virus which is an opportunity and a challenge to choose the right business strategy. Based on the results of the evaluation of previous studies and the analysis in this study, it is known that currently there are no sensors installed on the tools used for material transfer, communication between machines and machines (M2M) currently there is no data generated so no data is communicated, the interface between humans and machines (HMI) currently uses a local user interface through the Pro-St application and the interface on the fanuc machine, the current transportation system is moving materials to production machines, a manual transportation system, namely hand lifts, materials that have been packaged and will be stored in the warehouse using a forklift (machine for manual transportation), while the unit product movement from the fanuc machine already uses a conveyor, the transportation unit as an information carrier currently has a mechanism for individual identification of materials but the status of the material is not identified in the IT system, the current storage system for placing materials is still done intuitively and the identification process for storage locations is still listed manually on the blackboard. In order for the intralogistics system to implement intelligent supply chain and logistics based on industry 4.0, it is proposed to install sensors on the device to identify material movement and the sensor and actuator interaction data can be analyzed, network connections between devices for M2M communication, use of mobile user interfaces to monitor intralogistics processes and status. identified material in the IT system.